Joint Linear Precoder-Decoder Optimization over MIMO-CDMA Multipath Channels - Xiaolei Wang; Manikas, A. (2007 IEEE 18th International Symposium on Personal, Indoor and Mobile Radio Communications, 2007)
This paper addresses the problem of joint transmitter-receiver optimization in the downlink multiple input multiple output (MIMO) DS-CDMA systems over multipath fading channels. Both the transmitter and the receivers are equipped with antenna arrays and the precoding/decoding matrices can be designed to minimize the overall mean-squared-error (MSE) of the system subject to power constraint. The study is based on the spatio-temporal array (STAR) manifold concept. The performance of the proposed algorithm is supported by numerical simulations.